Competitiveness of Azerbaijan`S T&T industry and its impact on the regional economy - Ibrahimov, Eltun Yulat; Alakbarov, Ashraf Umud; Kerimova, Flora Bahlul; Alakberov, Rasul Safar (Edelweiss Applied Science and Technology, 2024)
In the last few years, the World Tourism Organization (UNWTO) has reported that the tourism industry has expanded significantly. According to the annual survey of economic impact, despite a very complex and turbulent economic situation in 2023-2024, the travel and tourism sector recorded significant growth in global GDP last year, and this is forecast to repeat in 2025. Overall, tourism will remain a promising engine for greater economic development and sustainable growth across a wide geographic spectrum, with a particular focus on strengthening the position of the developing world as a sector of the economy. This global trend has a positive effect on the tourism profile of Azerbaijan, whose tourism industry has achieved significant development in recent years. Against the background of the new realities created by the post-pandemic era, the noticeable increase in tourism indicators in Azerbaijan brings the regional perspectives of its economic competitiveness to the fore. This article describes how competitive is Azerbaijan's T&T industry in today's global economic challenges. The possibilities of the tourism system of Azerbaijan to influence the South Caucasus are also analyzed.